2007
DOI: 10.1177/0091270007306563
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics and Pharmacokinetics of AMG 531, a Thrombopoiesis‐Stimulating Peptibody, in Healthy Japanese Subjects: A Randomized, Placebo‐Controlled Study

Abstract: AMG 531 is a novel thrombopoiesis-stimulating peptibody being investigated for the treatment of chronic immune thrombocytopenic purpura. This double-blind, phase I study evaluated the safety, pharmacodynamics, and pharmacokinetics of AMG 531 in healthy Japanese men. Thirty subjects were randomly assigned 4:1 (AMG 531/placebo) to receive 1 dose of AMG 531 (0.3, 1, or 2 microg/kg) or placebo by subcutaneous injection; subjects were evaluated for 6 weeks. AMG 531 was generally well tolerated, with adverse events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 22 publications
(33 reference statements)
4
34
0
Order By: Relevance
“…The incidence of chronic ITP in adults in Japan is estimated to be 500-2000 cases annually, a rate of incidence similar to that seen in Western countries [1,21,22]. The safety, pharmacodynamics, and pharmacokinetics of romiplostim in Japanese adult patients were demonstrated in a phase I study and were consistent with those seen previously in healthy non-Japanese subjects [21].…”
Section: Introductionsupporting
confidence: 71%
“…The incidence of chronic ITP in adults in Japan is estimated to be 500-2000 cases annually, a rate of incidence similar to that seen in Western countries [1,21,22]. The safety, pharmacodynamics, and pharmacokinetics of romiplostim in Japanese adult patients were demonstrated in a phase I study and were consistent with those seen previously in healthy non-Japanese subjects [21].…”
Section: Introductionsupporting
confidence: 71%
“…90,[92][93][94][95][96][97][98] In 2 parallel, placebo-controlled, double-blind randomized phase 3 trials, romiplostim was given to 63 splenectomized and 62 non-splenectomized patients for 6 months. 93 An overall platelet response rate (Ն 4 out of 24 study weeks Ͼ 50 ϫ 10 9 /L) was observed in 79% and 88% of romiplostimtreated patients, compared with 0% and 14% in the respective placebo arms.…”
Section: Diagnosis and Treatment Of Immune Thrombocytopenia 173mentioning
confidence: 99%
“…A number of studies with TPOreceptor agonists have shown encouraging results in adults. 90,[92][93][94][95][96][97][98] However, no finalized studies in children are available to support the use of these agents in this patient population. Assuming that the long-term safety of these agents is confirmed, they could be used not only for children with chronic refractory ITP, but also in those with persistent but highly symptomatic disease resistant to usual first-line treatments.…”
Section: Treatment Options For Children With Persistent or Chronic Itpmentioning
confidence: 99%
“…[23][24][25] Japanese subjects when compared with previous studies of these agents in non-Japanese populations. [17][18][19]26) Haemophilia A is a relatively rare disease. 27) Although the A-LONG study is one of the largest global studies conducted in haemophilia A, there were 14 Japanese subjects included.…”
Section: Discussionmentioning
confidence: 99%